Biogas composition depending on the type of plant biomass used - M. Herout; J. Malaťák; L. Kučera; T. Dlabaja (Research in Agricultural Engineering, 2011)
The aim of the work is to determine and analyse concentrations of individual biogas components according to the used raw materials based on plant biomass. The measurement is focused on biogas production depending on input raw materials like maize silage, grass haylage and rye grain. The total amount of plant biomass entering the fermenter during the measurement varies at around 40% w/w, the rest is liquid beef manure. The measured values are statistically evaluated and optimised for the subsequent effective operation of the biogas plant. A biogas plant operating on the principle of wet anaerobic fermentation process is used for the measurement. The biogas production takes place during the wet fermentation process in the mesophile operation at an average temperature of 40°C. The technology of the biogas plant is based on the principle of using two fermenters. It follows from the measured results that maize silage with liquid beef manure in the ratio of 40:60 can produce biogas with a high content of methane; this performance is not stable. At this concentration of input raw material, the formation of undesirable high concentrations of hydrogen sulphide occurs as well. It is shown from the results that the process of biogas production is stabilised by the addition of other components of plant biomass like grass haylage and rye grain and a limitation of the formation of hydrogen sulphide occurs. It follows from the results that the maize silage should form about 80% w/w from the total amount of the plant biomass used.